2022
DOI: 10.1245/s10434-022-11761-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Indications for Sentinel Node Biopsy in Early-Stage Melanoma with the Advent of Adjuvant Systemic Therapy: An International, Multicenter Study

Abstract: Background Patients presenting with early-stage melanoma (AJCC pT1b-pT2a) reportedly have a relatively low risk of a positive SNB (~5–10%). Those patients are usually found to have low-volume metastatic disease after SNB, typically reclassified to AJCC stage IIIA, with an excellent prognosis of ~90% 5-year survival. Currently, adjuvant systemic therapy is not routinely recommended for most patients with AJCC stage IIIA melanoma. The purpose was to assess the SN-positivity rate in early-stage mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…group is no different from that of the SNBgroup. 4,26 Our data would indicate that the additional information afforded by the SNB for pT4b melanomas is limited, with no low-risk nodal micrometastatic disease in the SNB? group and no difference in DSS between the SNB-and SNB?…”
Section: Discussionmentioning
confidence: 93%
“…group is no different from that of the SNBgroup. 4,26 Our data would indicate that the additional information afforded by the SNB for pT4b melanomas is limited, with no low-risk nodal micrometastatic disease in the SNB? group and no difference in DSS between the SNB-and SNB?…”
Section: Discussionmentioning
confidence: 93%
“…The implementation of American Joint Committee on Cancer version 8 (AJCC8) criteria for melanoma increased the number of patients with thin melanomas (Breslow thickness ≤1 mm) undergoing SNLB versus AJCC7. However, this did not result in an increased rate of SNL‐positive results 22,23 . A retrospective study on SNLB in T1b melanomas ( n = 203) from Italy registered positive SNL in 2.3% of melanomas 0.8 < 1.0 mm, and in 0% of melanomas <0.8 mm with ulceration.…”
Section: Sentinel Lymphonodectomymentioning
confidence: 98%
“…However, this did not result in an increased rate of SNL-positive results. 22,23 A retrospective study on SNLB in T1b melanomas (n = 203) from Italy registered positive SNL in 2.3% of melanomas 0.8 < 1.0 mm, and in 0% of melanomas <0.8 mm with ulceration.…”
Section: Sentinel Lymphonodectomymentioning
confidence: 99%
“…25,26 Moreover, recent evidence suggests that 99% of patients with a T1b or T2a tumor with a positive SLN are considered stage IIIA and have 5-year untreated survival rates of 94%. 2,27 Therefore, identifying patients with a low likelihood of SLN positivity who can safely forego SLNB and have high survival rates has the potential to reduce unnecessary SLNBs, surgery-associated complications, and healthcare costs.…”
Section: Introduction Skinmentioning
confidence: 99%
“…Moreover, a recent study showed that patients with T1b/T2a tumors with a positive SLNB had survival equal to stage IIIA, with an associated 94% 5-year MSS. 2 Although recent discussion highlights that SLNB may have therapeutic benefits in SLNB-positive patients to control disease recurrence in the nodal basin, 3 these results highlight two important facts: 1) many patients may not need an SLNB and still have high survival rates and 2) recurrence or death prognostication in patients with a negative SLNB is critical to identify patients at high risk despite being SLN negative.…”
mentioning
confidence: 99%